Elementary Students' Academic Stress in Distance Learning by Gender and School Environment - Imroatul Hayyu Erfantinni (Madrasah: Jurnal Pendidikan dan Pembelajaran Dasar, 2023)
This study aims to reveal the academic stress experienced by elementary school students during the COVID-19 pandemic regarding the implementation of online learning from home. This research was conducted in Malang Raya by distributing questionnaires randomly with a total of 22 schools which were divided into 12 schools in urban areas and 10 schools in rural areas. The subjects were 236 students consisting of 103 male students and 133 female students. The instrument used is the academic stress scale developed by the researcher and has gone through the stages of validity and reliability. The lowest validity score is 0.363 and the highest validity value is 0.560 and the reliability score is 0.769. The data obtained show that the level of academic stress experienced by elementary school students in Malang Raya is in the low category of 98 students or 41.53%, then 126 students or 53.39% experience moderate stress, the rest are in the high category. experienced by 12 students or 5.09% of students only. Furthermore, if mapped based on rural and urban areas, the data obtained: from a total of 122 students who study in urban areas 9.8% experienced high levels of academic stress, 49.1% experienced moderate levels of academic stress and the remaining 40.9% students experienced academic stress at low level. Academic stress data obtained from students who study in rural areas are 0% of students experiencing high academic stress, 58.1% of students experiencing moderate level of academic stress, the remaining 41. 8% experienced a low level of academic stress. If mapped by gender, male students experience more academic stress than girls, although the difference is not too significant.